The Effect of the Implementation of Regional Financial Management Information System (SIMDA) and Human Resource Competence on the Quality of Financial Reports (Case Study On Regional Work Units In Sukabumi Regency) - Yunita, Nissa; Noor, Iqbal; Suherman, Acep (Journal of Management, Economic, and Accounting, 2023)
This study aims to determine the effect of applying regional financial management information systems (SIMDA), competence of human resources on the quality of financial reports. And the independent variables used in this study are the Implementation of the Regional Financial Management Information System (SIMDA), Competence of Human Resources, while the dependent variable used is the Quality of Financial Statements. And the method used is quantitative and associative methods. The data collection technique used in this study was in the form of a questionnaire or questionnaire and used a Likert scale. And for the sample used there are 70 samples from 10 agencies that are in the Regional Work Unit (SKPD). The results of this study indicate that the Regional Financial Management Information System (SIMDA) has a significant and positive effect on the quality of financial statements. And this is indicated by a significant value of 0.000 <0.05 and a t-count value of 4.012 > 1.996, while for Human Resource Competence it has a significant and positive effect on the Quality of Financial Statements. And this is indicated by a significant value of 0.024 <0.05 and a calculated t value of 2.306 > 1.996, which means that both variables have a significant and positive effect on the quality of financial statements.